1977
DOI: 10.1021/ja00464a043
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium nuclear magnetic resonance investigation of the dipalmitoyl lecithin-cholesterol-water system

Abstract: molecule lies along the z axis and the second molecule lies along the intermolecular y axis. The most important contribution to the dispersion energy involves a pure dx2-yi virtual orbital of the first molecule. The dxy orbital of the first molecule is also important. Other important virtual orbitals of the first molecule generally have a large coefficient corresponding to some d components. The d functions are of less interest when the molecule lies along the intermolecular}' axis. For instance in the linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
56
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 0 publications
12
56
0
Order By: Relevance
“…Early investigations [1,79,80] utilized site-specific labeling strategies, whereby synthetically accessible C–H sites along the acyl chain of the molecule, the glycerol backbone, and choline headgroup were replaced by C– 2 H bonds. These 2 H NMR studies revealed a systematic variation of the lineshapes as a function of segmental position, due to variations in the degree of motional averaging.…”
Section: Solid-state Nmr Spectra Exhibit Couplings That Allow Ordementioning
confidence: 99%
“…Early investigations [1,79,80] utilized site-specific labeling strategies, whereby synthetically accessible C–H sites along the acyl chain of the molecule, the glycerol backbone, and choline headgroup were replaced by C– 2 H bonds. These 2 H NMR studies revealed a systematic variation of the lineshapes as a function of segmental position, due to variations in the degree of motional averaging.…”
Section: Solid-state Nmr Spectra Exhibit Couplings That Allow Ordementioning
confidence: 99%
“…An important general observation is that under conditions for which a bilayer would be in the liquid crystalline phase, addition of cholesterol increases lipid chain orientational order and thus bilayer thickness. [1][2][3][4][5][6][7] Cholesterol also lowers the temperature below which rapid axially symmetric lipid reorientation freezes out. 5,7 NMR and other techniques such as neutron scattering and vibrational spectroscopy have also been used to examine cholesterol orientation, dynamics, and position within bilayers.…”
Section: Introductionmentioning
confidence: 99%
“…The method has been applied mainly to bilayers containing the phosphocholine head group, i.e. 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) [3,4], 1 -palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) [ 5,6], DPPC plus cholesterol [7], 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) [8] and egg-yolk lecithin [9]. In addition, a deuterium order profile has been published for Acholeplasma laidlawii membranes biosynthetically enriched with deuterated palmitate [lo].…”
Section: Introductionmentioning
confidence: 99%